Phytochemical Study of Steroidal Sapogenin â€œTigogeninâ€ Present in the Leaves of Agave americana Cultivated in Iraq - bijps; Ruaa M. Abrahem; Zainab J. Awad (College of Pharmacy University of Baghdad, 2017)
The presence of the most important steroidal sapogenin â€œTigogeninâ€ in the leaves of Agave americana  cultivated in Iraq was detected. The absence of any study concerning the Tigogenin content of this medicinal plant in Iraq, and the industrial importance of Tigogenin depending on its role as a precursor in the synthesis of some steroidal drugs, acquired this study its value. This search include extraction,  isolation,  purification and dentification of Tigogenin from the leaves of Agave americana. Extraction of this compound was carried out using two methods. Identification of this compound is carried out by using thin layer chromatography (TLC) where three different mobile phase have been used. Detection is done by using  Libermann â€" Burchard reagent .High performance liquid chromatography (HPLC) is also used  for further identification of tigogenin and then this steroidal saponin was isolated and purified. Isolated Tigogenin  is identified by using Thin layer chromatography (TLC), melting point (M.P.),  Infrared spectroscopy (IR) and High performance liquid chromatography (HPLC) . This study confirms the presence of Tigogenin in the leaves of Agave americana cultivated in Iraq. Also the result of this study showed that the  second extraction method is better, because the amount of  both tigogenin and extract obtained from method No.2 are  more than one extraction method.